Retorik og lykke - Madsen, Carsten (K&K - Kultur og Klasse, 2016)
This article maps out the function of and interrelationship between the rhetorical and the ethical uses of happiness (eudaimonia) in Aristotle’s Rhetoric and Nicomachean Ethics and within the framework of the democratic polis in Greek antiquity. Deliberations about happiness are claimed to interdependently organize Greek rhetoric and structure the moral character (ethos) of people. Through an analysis of Pericles’ eulogy it is demonstrated how epideictic oratory can function as an argumentative deliberation that simultaneously advances happiness as a political and a personal goal. It is further proposed that the interrelationship between rhetoric and ethics makes it possible to critically test any rhetorical statement in terms of happiness. Finally, with reference to Alisdair MacIntyre, it is briefly suggested that central arguments of contemporary virtue ethics could be strengthened by taking rhetorical deliberation about happiness into account, just as rhetorical theories about ethos could benefit from the insights of contemporary eudaimonism.